(3CbGhjd GdChGFd aj WHGFY GdCZPjI hbhGgGs - (3ESMGb Hf SdjeGf GdGSQGFjdj, CHh jYbhH,J (B320 (3g` s ((3YHO Gddg Hf CMeO Hf GdHGTbi s)
(3ChdgG (B:s
(3dGMhd hdG bhI EdG HGddg , GdYdi GdYXje , bO CJjfG ai GdLRA GdChd ef cJGHfG gPG Ydi eG GQOfG ef GdOdGFd s
(3BNQgG (B:s
(3bdY LQHgG HEPf Gddg Ld hYR aLR GdLRA GdKGfi ef cJGH GdCZPjI s
(3GdeLdO GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B22 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs